(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to determine the effects ofcompost on growth of Acacia nilotica, A. seyal, A. senegal and A. tortilisseedlings. It was conducted in Khartoum University Farm, duringDecember 1999- January 2002. Compost was prepared in a pit from forestlitter and poultry manure. Four quantities of compost were added to asandy soil and a silty soil (% volume): zero, 25%, 50% and 75%. Theblends were packed in polythene bags prior to transplanting. The compostwas slightly acidic, non-saline, and rich in nutrients and had high waterholding capacity. The compost negatively affected acacia seedgermination percentage by 1.5 to 5.3 folds compared to the mineral soils.Shoot height in the compost-sand mixes increased significantly ascompared to the unamended sandy soil by 1.4 to 2 folds. Root length wasgenerally lower in the compost treatments. Shoot and root biomass in thecompost media was significantly higher than in the sandy soil andincreased by 3 to 7 and 1.5 to 3.0 folds, respectively. In the silt-compostmixes, seedlings’ shoot heights were significantly greater than in theunamended silty soil. Root lengths in the silt-compost mixes were notsignificantly different from those in the silty soil. Shoot and root biomassin the silt-compost mixes was not significantly different from that in theunamended silty soil. Compost effects on seedlings’ growth occurred in